A Polysulfides‐Confined All‐in‐One Porous Microcapsule Lithium–Sulfur Battery Cathode. Issue 41 (12th September 2021) - Liu, Jinyun; Zhu, Mengfei; Shen, Zihan; Han, Tianli; Si, Ting; Hu, Chaoquan; Zhang, Huigang
Abstract: Developing emerging materials for high energy‐density lithium–sulfur (Li–S) batteries is of great significance to suppress the shuttle effect of polysulfides and to accommodate the volumetric change of sulfur. Here, a novel porous microcapsule system containing a carbon nanotubes/tin dioxide quantum dots/S (CNTs/QDs/S) composite core and a porous shell prepared through a liquid‐driven coaxial microfluidic method as Li–S battery cathode is developed. The encapsulated CNTs in the microcapsules provide pathways for electron transport; SnO2 QDs on CNTs immobilize the polysulfides by strong adsorption, which is verified by using density functional theory calculations on binding energies. The porous shell of the microcapsule is beneficial for ion diffusion and electrolyte penetration. The void inside the microcapsule accommodates the volumetric change of sulfur. The Li–S battery based on the porous CNTs/QDs/S microcapsules displays a high capacity of 1025 mAh g −1 after 100 cycles at 0.1 C. When the sulfur loading is 2.03 mg cm −2, the battery shows a stable cycling life of 700 cycles, a Coulombic efficiency exceeding 99.9%, a recoverable rate‐performance during repeated tests, and a good temperature tolerance at both −5 and 45 °C, which indicates a potential for applications at different conditions. Abstract : A porous microcapsule containing carbon nanotubes/tin dioxide quantum dots/sulfur (CNTs/QDs/S) core and porous shell as Li–S battery cathode is developed. CNTs provide pathways for electron transport; QDs on CNTs immobilize the polysulfides, which are verified through density functional theory calculations. The porous CNTs/QDs/S microcapsule cathode displays long cycling life and good temperature tolerance.